Entrepreneurial intention studies: A hybrid bibliometric method to identify new directions for theory and research - Loi Michaela; Castriotta Manuel; Dubard Barbosa Saulo; Di Guardo M. Chiara; Fayolle Alain (Wiley, 2026)
Fragmentation is the main obstacle to scientific progress on entrepreneurial intention. To address this issue, we systematise the current literature with a hybrid bibliometric method that combines co-citation and bibliographic coupling analysis for the first time in entrepreneurial intention studies to show the field’s knowledge base and research fronts and to examine how divergent perspectives have challenged the core knowledge of the field. We highlight three recurring dimensions of entrepreneurial intention studies: (1) personal factors, (2) social factors and (3) investigational settings. In addition to introducing new constructs, divergent perspectives have emphasised the interplay between these components and challenged the mechanisms connecting them. Based on these findings, we extend previous classifications in the literature by providing a framework that integrates divergent perspectives with the field’s knowledge base, helping establish future research avenues and improving the theorising process of entrepreneurial intention.